2019
DOI: 10.1111/1745-9133.12441
|View full text |Cite
|
Sign up to set email alerts
|

Public opinion and correctional privatization

Abstract: Research Summary: Slightly more than half of all states and the federal government currently have contracted with private prison corporations for the incarceration of some of their correctional populations. We use the literature on privatization of prisons to argue that we know surprisingly little about the public's perception of this phenomenon. We summarize what is known from the thin body of research into public opinion in the correctional domain, and then we argue for an expanded research agenda to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…We know surprisingly little about what the public thinks of correctional privatization (Frost, Trapassi, & Heinz, ). Overall, support for prison privatization seems mixed.…”
Section: Politics Influence Privatizationmentioning
confidence: 99%
“…We know surprisingly little about what the public thinks of correctional privatization (Frost, Trapassi, & Heinz, ). Overall, support for prison privatization seems mixed.…”
Section: Politics Influence Privatizationmentioning
confidence: 99%
“…For example, news stories may instead reflect the views of the public. That said, the public’s views on private prisons remain largely unknown (Frost et al, 2019). Similarly, it may be that the stories give primary weight to politicians’ views.…”
Section: Resultsmentioning
confidence: 99%
“…Based on extant empirical research on private prisons, it is unclear whether they are more or are less effective or cost-efficient than public prisons. It is also largely unknown where the public stands on the use of private prisons (Frost et al, 2019). Against this backdrop, scholarship has shown that the debate about private prisons entails a more complex calculus than simply cost-efficiency or public views about the ethics of relying on private companies to manage punishment (e.g., Austin & Coventry, 2001; Lindsey et al, 2016; C.…”
Section: Introductionmentioning
confidence: 99%
“…Some approaches, however, may help to shed light on them. For example, public opinion surveys can help to illuminate the conditions under which citizens support privatization (see Frost, Trapassi, & Heinz, , this issue). Perhaps support would be enhanced if private entities had to demonstrate greater effectiveness in reducing recidivism or improving reentry outcomes.…”
Section: Conceptual Framework For Reframing the Privatization Debatementioning
confidence: 99%